Proceedings of the 24th Conference on Computational Natural Language Learning 2020
DOI: 10.18653/v1/2020.conll-1.32
|View full text |Cite
|
Sign up to set email alerts
|

Discourse structure interacts with reference but not syntax in neural language models

Abstract: Language models (LMs) trained on large quantities of text have been claimed to acquire abstract linguistic representations. Our work tests the robustness of these abstractions by focusing on the ability of LMs to learn interactions between different linguistic representations. In particular, we utilized stimuli from psycholinguistic studies showing that humans can condition reference (i.e. coreference resolution) and syntactic processing on the same discourse structure (implicit causality). We compared both tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
(51 reference statements)
3
14
0
Order By: Relevance
“…Prior work has noted competing generalizations influencing model behavior via the distinction of non-linguistic vs. linguistic biases (e.g., Mc-Coy et al, 2019;Davis and van Schijndel, 2020a;Warstadt et al, 2020b). The findings in Warstadt et al (2020b), that linguistic knowledge is represented within a model much earlier than attestation in model behavior, bears resemblance to our claims.…”
Section: Related Worksupporting
confidence: 83%
See 3 more Smart Citations
“…Prior work has noted competing generalizations influencing model behavior via the distinction of non-linguistic vs. linguistic biases (e.g., Mc-Coy et al, 2019;Davis and van Schijndel, 2020a;Warstadt et al, 2020b). The findings in Warstadt et al (2020b), that linguistic knowledge is represented within a model much earlier than attestation in model behavior, bears resemblance to our claims.…”
Section: Related Worksupporting
confidence: 83%
“…Given that all the investigated stimuli were disambiguated by gender, we categorized our results by the antecedent of the pronoun and the IC verb bias. We first turn to English and Chinese, which showed an IC bias in line with existing work on IC bias in autoregressive English models (e.g., Upadhye et al, 2020;Davis and van Schijndel, 2020a). We then detail the results for Spanish and Italian, where only very limited, if any, IC bias was observed.…”
Section: Experimental Stimuli and Measuresmentioning
confidence: 55%
See 2 more Smart Citations
“…While they did not find strong evidence for a correlation to human-based results in this respect, they did observe that in the context of connective because PLMs assigned lower probability to subjectreferring pronouns for an object-biasing verb as compared to a subject-biasing verb. Davis and van Schijndel (2020) observed that GPT2-XL (Radford et al, 2019) encodes some level of IC bias in its representations (measured in terms of similarity between the representation of the pronoun and its two potential referents) and its decision on how to resolve a referent at prediction time is weakly influenced by that. They took the analysis one step further and looked at whether GPT2-XL uses IC information to resolve relative clause attachment, which in humans is conditioned by IC bias-no evidence was found to suggest that that was the case.…”
Section: Related Workmentioning
confidence: 99%